REKONSTRUKSI ASAS PUBLISITAS DAN KEWAJIBAN ADMINISTRATIF KURATOR DALAM HUKUM KEPAILITAN: ANALISIS PUTUSAN MK NO. 74/PUU-XXIV/2026 - Maddenleo T Siagian; Purgito Purgito; Fransiskus Litoama (JOURNAL IURIS SCIENTIA, 2026)
Decision of the Constitutional Court No. 74/PUU-XXIV/2026 dated April 29, 2026 introduces a significant shift in the interpretation of Article 74 paragraph (1) of Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (PKPU), particularly by expanding the procedural obligations of trustees (curators) in submitting bankruptcy reports. The Court held that curators are not only required to file reports at the Commercial Court Registry, but must also deliver copies of such reports directly to debtors and creditors through various communication channels. This study aims to critically examine the legal and practical implications of this expanded interpretation on the principles of efficiency, effectiveness, and legal certainty within the Indonesian bankruptcy system. This research employs a normative legal method using statutory, conceptual, and case-based approaches, focusing on the Constitutional Court decision. The findings indicate that the expanded administrative obligations imposed on curators may increase bankruptcy costs, create excessive administrative burdens, and reduce the value of the bankruptcy estate available for distribution to creditors. In addition, the ruling raises potential legal uncertainty regarding the validity and evidentiary status of electronically delivered notifications. The decision also reflects elements of judicial activism, as it extends into technical regulatory matters that arguably fall within the competence of the legislature or judicial administrative regulators. Therefore, strengthening transparency in bankruptcy proceedings would be more appropriately achieved through the optimization of integrated digital court information systems rather than by expanding individual notification duties imposed on curators.